1993
DOI: 10.1002/arch.940230106
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lipids in the salivary glands of Amblyomma americanum (L.): Detection of a high level of arachidonic acid

Abstract: Analysis of lipids in salivary glands of the lone star tick, Amblyomma americanum, demonstrated that arachidonic acid (20:4, n-6) comprises 8% of all fatty acids identified by gas chromatography. The occurrence of arachidonic acid and other C20 polyunsaturated fatty acids in tick salivary glands was confirmed by gas chromatography-mass spectrometry. Arachidonate is located entirely in the phospholipid fraction and is associated exclusively with phosphatidylcholine (PC) and phosphatidylethanolamine (PE). Saliva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The lipid profile of the salivary glands of blood-sucking arthropods has been examined in detail for the lone-star tick, Amblyomma americanum (30). In this case careful work has been undertaken in analyzing the arachidonic acid (AA) profile associated with each lipid present in the salivary glands of the tick, especially phospholipids, and in relating AA levels to the occurrence of salivary prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…The lipid profile of the salivary glands of blood-sucking arthropods has been examined in detail for the lone-star tick, Amblyomma americanum (30). In this case careful work has been undertaken in analyzing the arachidonic acid (AA) profile associated with each lipid present in the salivary glands of the tick, especially phospholipids, and in relating AA levels to the occurrence of salivary prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…Cultured salivary glands accumulated both PGF and PGE2 with increasing time of incubation suggesting an ability of the salivary glands to synthesize prostaglandins, at least when cultured in vitro. Shipley et al ( 1993) found that salivary glands of A americanum female ticks contained relatively high levels of arachidonic acid, the precusor of prostanoids. Bowman et al(1993) also demonstrated that PGE2, PGF2a and PGD2 existed with PGE2 at the highest concentration in secreted saliva of A. americanum following labelling of salivary glands in vivo with radiolabelled arachidonic acid.…”
Section: Prost Ano Id Bio Synthesismentioning
confidence: 95%
“…Free arachidonic acid may be converted into PGs via the cyclooxygenase pathway in tick salivary glands (Higgs et al, 1976;Dickenson et al, 1976;Shemesh et al, 1979;Ribeiro et al, 1985Ribeiro et al, , 1988Ribeiro et al, , 1992Bowman et al, 1993;Shipley et al, 1993). The occurrence of PGs in tick salivary glands may indicate an autocrine role for these compounds in ticks.…”
Section: Objectives Of This Studymentioning
confidence: 99%
“…The activity is removed by incubation with 15-hydroprostaglandin dehydrogenase (Dickinson et al, 1976). Approximately 75% of the arachidonic acid is in the sn-2 position of PC and PE (Shipley et al, 1993). Analysis of lipids in salivary glands of the lone star tick, Amblyomma americanum, determined that arachidonic acid (20:4, n-6) comprises 8% of all fatty acids identified by gas chromatography.…”
Section: A Lipidsmentioning
confidence: 99%